Comparison of the post-tensioned, solid, hollow block, and flat slabs in terms of economy considering different span lengths - Ahmad, Omar; Sadeghi, Kabir; Nouban, Fatemeh (Zielona Góra: Uniwersytet Zielonogórski)
From among the several types of slabs, there is uncertainty about the most cost-effective one for structures with short, medium, and long spans. A study comparing the cost of the solid, flat, hollow block (HB), and post-tensioned (PT) slabs for 4, 6, and 8m spans was conducted using SAFE software. For each span length, the total quantities of concrete and steel bars were found and compared for 4 slabs. Then, the total cost of steel bars, concrete, blocks, tendons, and formwork was tabulated and compared.
Keywords: solid slab; HB slab; flat slab; PT slab; cost